2006
DOI: 10.1093/fampra/cml041
|View full text |Cite
|
Sign up to set email alerts
|

Can the Asthma Control Questionnaire be used to differentiate between patients with controlled and uncontrolled asthma symptoms? A pilot study

Abstract: Our results show that discrimination between asthma patients with controlled and uncontrolled asthma symptoms, based on the ACQ, is possible with a reasonable margin of test inaccuracy. Thus, the ACQ may be an important tool for health care professionals who aim to optimize the level of asthma control in their patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…In that study, the authors also found that the questionnaire discriminated well between patients with different degrees of symptom intensity and frequency. 18 In the present study, a positive relationship was also observed between scores on the CAN questionnaire and patient or carer overall perceptions of asthma control.…”
Section: Discussionsupporting
confidence: 72%
“…In that study, the authors also found that the questionnaire discriminated well between patients with different degrees of symptom intensity and frequency. 18 In the present study, a positive relationship was also observed between scores on the CAN questionnaire and patient or carer overall perceptions of asthma control.…”
Section: Discussionsupporting
confidence: 72%
“…In a previously reported pilot study, 13 we established an ACQ cutoff value for identifying patients with asthma who have suboptimal control of their symptoms. A sum score of 3 points or less best indicated good asthma symptom control, having a sensitivity of 84% and a specifi city of 76%.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 13 we found that the Asthma Control Questionnaire (ACQ) [14][15][16] can be used to distinguish asthma patients with good symptom control from those with suboptimal symptom control. The aim of the current study was to investigate whether a mailing of the ACQ can be used to trace asthma patients with suboptimal symptom control in the family practice population.…”
Section: S17mentioning
confidence: 99%
See 2 more Smart Citations